Poetas románticos y neoclásicos - Burbano, José Ignacio (Biblioteca Ecuatoriana Mínima. La Colonia y la República, 1960)
Contiene: Rafael Carvajal.Gabriel García Moreno, Miguel Riofrio, Francisco Javier Salazar Arboleda, Ramón Samaniego Palacio, Dolores Veintimilla de Galindo, Numa Pompilio LLona, Juan León Mera, Miguel Angel Corral, Julio Zaldimbide,Luis Cordero, Vicente Piedrahita, Quintiliano Sanchez, Abelardo Moncayo, Miguel Moreno, Julio Matovelle, Juan Abel Echeverria, Honorato Vazquez, Rafael María Arizaga, Manuel Polo, Adolfo Benjamin Serrano, Antonio Toledo.